Analysis of the Influence of Open Unemployment Rate, Poverty Rate, and Economic Growth on the Human Development Index in Sleman Regency - Kawashita, I Wayan Rioichi; Marseto, Marseto (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to identify the influence of the open unemployment rate, poverty rate, and economic growth on the Human Development Index (HDI) in Sleman Regency. Data from 2011 to 2020 were analyzed to understand the relationship between independent variables and HDI as the dependent variable. The multiple linear regression analysis method was employed, supported by classical assumption tests such as normality, autocorrelation, multicollinearity, and heteroskedasticity. The results indicate that the open unemployment rate and the poverty rate have a significant influence on HDI, while economic growth does not have a significant impact. Simultaneously, all three variables collectively affect HDI. Policy implications include the crucial role of the government in improving infrastructure and providing education to the community. It is suggested that the community supports government programs for progress and welfare. Further research can explore additional variables influencing HDI. This study contributes to understanding the factors influencing human development in Sleman and can serve as a foundation for future research.